(untitled) (Al-Qamar, 2023)
It is an irrefutable fact that any system of the world is incomplete without education, no nation can gain respect without education. Knowledge is light, ignorance is darkness. Knowledge is the means through which man can attain the blessing of Allah Almighty. Therefore, we must equip our children with Islamic teachings. Due to knowledge, the feelings of godliness, worship, love, sincerity, sacrifice, service to the people, loyalty and compassion arise in life. This paper argues that prominent people of every class of society have important responsibilities in the creation and promotion of knowledge. If all these people work together to create and flourish knowledge, then a scientific and social revolution can take place in the society.